Tribal Clashes and its Impact on Economic Development: A Case Study of District Shikarpur-Sindh-Pakistan - Phulpoto, Najma Noor; Shaikh, Faiz M; Shah, Aisha Bashir (Journal of Asian Business Strategy, 2012)
This research investigates the Tribal clashes and its impact on Economic development of District Shikarpur. Data were collected from 400 respondents from Shikarpur and their vicinity. A structural questionnaire was developed for the reliability and validity of the data. It was revealed that the derth of security and absence of good governance generate the problems for the business development in District Shikarpur. It was further revealed that Government is not providing security to the business oriented firm to invest in Shikarpur.